Immunochemical analysis of uridine diphosphate-glucuronosyltransferase in four patients with the Crigler-Najjar syndrome type I. - van Es, H H (1990)
The functional heterogeneity of uridine diphosphate-glucuronosyltransferase (UDPGT) and its deficiency in human liver were investigated. The monoclonal antibody (MAb) WP1, which inhibits bilirubin and phenol-glucuronidating activity, was used to immunopurify UDPGTs from human liver. Purified UDPGTs were injected into mice to obtain new MAbs. Immunoblotting of microsomes with MAb HEB7 revealed at least three polypeptides in liver (56, 54, and 53 kD) and one in kidney (54 kD). In liver microsomes from four patients (A, B, C, and D) with Crigler-Najjar syndrome type I (CN type I), UDPGT activity towards bilirubin was undetectable (A, B, C, and D) and activity towards phenolic compounds and 5-hydroxytryptamine either reduced (A and B) or normal (C and D). UDPGT activity toward steroids was normal. Immunoblot studies revealed that the monoclonal antibody WP1 recognized two polypeptides (56 and 54 kD) in liver microsomes from patient A and none in patient B. With HEB7 no immunoreactive polypeptides were seen in these two patients. Patient C showed a normal banding pattern and in patient D only the 53-kD band showed decreased intensity. These findings suggest considerable heterogeneity with regard to the expression of UDPGT isoenzymes among CN type I patients.